Regulation of cell death in cancer—possible implications for immunotherapy - Fulda, Simone (Frontiers in Oncology, 2013)
Since most anticancer therapies including immunotherapy trigger programmed cell death in cancer cells, defective cell death programs can lead to treatment resistance and tumor immune escape. Therefore, evasion of programmed cell death may provide one possible explanation why cancer immunotherapy has so far only shown modest clinical benefits for children with cancer. A better understanding of the molecular mechanisms that regulate sensitivity and resistance to programmed cell death is expected to open new perspectives for the development of novel experimental treatment strategies to enhance the efficacy of cancer immunotherapy in the future.